2023
DOI: 10.1108/dlp-04-2023-0025
|View full text |Cite
|
Sign up to set email alerts
|

Rural accessibility to digital libraries: requirements and challenges

Mapheto J. Mamabolo,
Oluwole Olumide Durodolu

Abstract: Purpose This study aims to determine the requirements and find out the challenges for the use of digital library services for rural areas of Capricorn District Municipality, Limpopo province. The research questions of the study are: What are the requirements for the use of digital library services in rural areas of Capricorn District Municipality? What are the challenges of accessing digital library services in rural areas? Design/methodology/approach Data was analysed thematically and deductively in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Digital economic development tends to be spatially nonlinear [ 32 ]. Wang and Cen (2022) found that the nonlinear characterization of the increasing marginal effect of the digital economy on innovation efficiency [ 33 ].…”
Section: Theoretical Framework and Research Hypothesismentioning
confidence: 99%
“…Digital economic development tends to be spatially nonlinear [ 32 ]. Wang and Cen (2022) found that the nonlinear characterization of the increasing marginal effect of the digital economy on innovation efficiency [ 33 ].…”
Section: Theoretical Framework and Research Hypothesismentioning
confidence: 99%